Evaluation of Patients’ Knowledge and Adherence to Clopidogrel Therapy Post Percutaneous Coronary Intervention - Raheem, Zainab; Mohammed, Tahseen R. (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To evaluate patients’ knowledge and their adherence to clopidogrel therapy post percutaneous coronary intervention (PCI) and to find out the relationship between patients’ knowledge and their adherence to clopidogrel therapy post PCI.Methodology: A descriptive study  was carried out at Al- Nasiriyah Heart Center in Thi-Qar Governorate for the period of May 19th 2022 to October 25th 2022. A non-probability sampling was used to se;ect (50) patients after their Percutaneous Coronary Intervention. The study instrument was used to collect data which was composed of three parts of sociodemographic characteristics, patients’ knowledge regarding clopidogrel therapy post percutaneous coronary intervention PCI which was comprised of (16) questions and General Medication Adherence Scale which was consisted of (11) questions. Data were analyzed using IBM SPSS version 26. Descriptive and inferential data analysis were utilized to analyze the data.Results: The study indicated that patients had knowledge deficit (82%) and low adherence (84%) to Clopidogrel therapy.Conclusion: The study concluded that there was a lack of patients’ knowledge and adherence to clopidogrel therapy post percutaneous coronary intervention.Recommendation: The study recommended that establishing an  educational program regarding cardiac medications, such as Clopidogrel to  increase patients’ knowledge and improve their adherence post percutaneous coronary intervention.